Clinical and epidemiological characteristics of patients in the head and neck surgery department of a university hospital - Ruback, Maurício José Cabral; Galbiatti, Ana Lívia; Arantes, Lidia Maria Rebolho Batista; Marucci, Gustavo Henrique; Russo, Anelise; Ruiz-Cintra, Mariangela Torreglosa; Raposo, Luiz Sérgio; Maniglia, José Victor; Pavarino, Érika Cristina; Goloni-Bertollo, Eny Maria (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVES: Head and neck cancer is the fifth most common type of cancer worldwide. The objective of this study was to evaluate the clinical and epidemiological parameters in a head and neck surgery service. DESIGN AND SETTING: Cross-sectional study using patients’ records, developed in otolaryngology and head and neck department of a university hospital in the northwest of the state of São Paulo. METHODS: A total of 995 patients in the head and neck surgery service between January 2000 and May 2010 were evaluated. The variables analyzed included: age, gender, skin color, tobacco and alcohol consumption, primary site, staging and histological tumor type, treatment and number of deaths. RESULTS: The disease was more frequent among men (79.70%), smokers (75.15%) and alcohol abusers (58.25%). The most representative sites were oral cavity (29.65%) and larynx (24.12%) for the primary site; squamous cell carcinoma (84.92%) was the most frequent histological type, and surgery (29.04%) and radiotherapy (14.19%) were the most common treatments. CONCLUSION: The cancer that affects patients assisted by the head and neck surgery service occurs mainly men, smokers and alcohol abusers, and the oral cavity and larynx are the sites with the highest incidence. The high rate of patients with stages III and IV indicates late diagnosis by the treatment centers, which reflects the need for prevention education campaigns for early diagnosis of the disease.